Parenting Psikoedukasi Dalam Mendukung Perkembangan Sosial Dan Emosional Anak Usia Pra Sekolah Di Kota Surakarta - Insiyah Insiyah; Endang Caturini Sulistyowati ((JKG) Jurnal Keperawatan Global, 2019)
Background: Children in kindergarten are experiencing rapid growth and development. Supporting child development is not only the responsibility of the government but also the responsibility of parents, teachers and the surrounding community. Parents are expected to have a good understanding of the psychological child so that they can provide care and education that allows children to grow and develop according to their age. This study aims to determine the effect of parenting psychoeducation on the social and emotional development of pre-school children. Methods: This research used the method of "quasi experiment pre-post test with one group" with a total sample of 63 pre-school age children. Sampling was done using Non Randomized One Group Pretest Postest Design. Research data analysis was performed using SPSS version 23. Results: The results showed that preschool age children numbered 63 people consisting of 60.3% (38) people were male and the rest were female 39.7% (25). There was an increase in social development in preschool children whose parents received significantly higher parenting psychoeducation (p value 0,000) There was an increase in emotional development in pre-school children whose parents received significantly higher parenting psychoeducation (p value 0,000). Conclusion: The conclusion showed that there was a parenting psychoeducation effect on parents on social and emotional development of pre-school age children. Keywords: Psychoeducation, Social and Emotional Development, Pre School Children